The skin in Behçet's disease: Mucocutaneous findings and differential diagnosis. Issue 1 (14th February 2022) - Vural, Seçil; Boyvat, Ayşe
Abstract: Behçet's disease (BD) is a chronic multisystemic inflammatory disease with vasculitis and skin findings. Attacks and remissions characterize the course of the disease. In general, the disease activity decreases with advanced age. Skin symptoms are characteristic of BD and they are the most common findings in the course of the disease. The earliest sign of the disease is almost always recurrent oral aphthous ulcers. Genital ulcers are very specific for BD and they are the equivalent of oral ulcers in the genital area. The most common location is labium majus in females and scrotum in males. The papulopustular lesions are mainly observed on the lower extremities in BD patients. Erythema nodosum‐like lesions and superficial thrombophlebitis are relatively common skin findings. Extragenital ulcerations presenting on the intertriginous area are rare but specific for the disease. The clinical skin manifestations are crucial for the diagnosis of BD, as there is no pathognomonic confirmatory laboratory test. Abstract : Behçet's disease skin findings.